(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the modern interpretation of the music and stage performance «Aksatkyn & Myrzy uul» by the «Ustatshakirt» Center, showcasing the integration of traditional music forms into modern art to preserve and develop Kyrgyz traditional culture amidst globalization. Through a blend of music, theater, and multimedia, the production bridges cultures, epochs, and traditions, appealing to a wide audience. This unique fusion incorporates elements of musical theater, jazz improvisation, and multimedia, led by Taalai Beysheev to create a mediating link between traditional, academic, and contemporary music. The performance, based on Barpa Alykulov’s version of «Aksatkyn and Kulmyrza,» emphasizes generational dialogue and education through the participation of performers of various ages and professional backgrounds. The innovative «dastan-musical» interpretation enriches Kyrgyz composer’s art heritage and expands the theater repertoire.